Characterization of Fern Spores in the Treehouse Ecotourism Area of Waai Village, Central Maluku - Hakapaa, Adriana; Sahureka, Thalia; Latue, Philia C.; Sinay, Hermalina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Ferns (Pteridophyta) are vascular plants possessing true roots, stems, and leaves, and they reproduce by spores, whose morphological characteristics constitute critical diagnostic features for taxonomic identification. The Treehouse Ecotourism Area of Waai Village harbors significant fern diversity that is increasingly threatened, rendering spore characterization an essential approach for conservation, species identification, and the advancement of scientific research as well as ecotourism development. The aim of this study was to examine the characteristics of fern spores found in the Tree houses ecotourism area, Waai Village, Central Maluku, as a contribution to conservation efforts, ecotourism education, and the enrichment of fern micromorphological references in Maluku. The research was conducted using an exploratory survey method along an approximately 20-km trail from the entrance gate to the tourism site. Fern leaf samples were collected to observe soral and spore structures using whole-mount preparations, followed by acetolysis, washing, staining, and mounting procedures. Characterization was carried out microscopically, focusing on sorus form, position, and color, as well as spore morphology, including grain shape and aperture type. The results revealed nine spore-bearing fern species: Pteris vittata, Cyclosorus interruptus, Pteridium aquilinum, Blechnopsis orientalis, Sticherus underwoodianus, Nephrolepis exaltata, Lygodium microphyllum, Lygodium flexuosum, and Pityrogramma calomelanos. The observed soral characters varied from linear, laminar, and granular to powdery forms, and were located either abaxially or adaxially. Spore shapes included oval, round, and triangular forms, with both monolete and trilete laesura types. This variation in soral and spore characteristics provides a basis for the taxonomic identification of ferns and supports further studies in biogeography and phylogenetics.